Growth enhancement of Brazilian green dwarf coconut seedlings by Bacillus cereus in coconut fiber substrate is associated with changes in metabolism and reduction in fertilization - Silva, Gisele (2020)
The objective of this work was to evaluate the effects of application of Bacillus cereus combined with the use of substrate and reduction in conventional fertilization on the growth of green dwarf coconut seedlings in Brazil, the Santa Isabel nursery in the state of Pará, Brazil. The experiment design was completely randomized with four treatments: soil+100% fertilizati+on; soil+ 50% fertilization + B. cereus; coconut fiber+100% of fertilization; and coconut fiber+33% of fertilization plus B. cereus, with 5 replications. Biochemical tests were performed with B. cereus and in the field where the following were evaluated: biometrics, hormonal and nutritional profile compared by t Test (P <0.05). Isolate B. cereus produced siderophores, IAA and phosphate solubilizer. In the field, the treatmwxent with inoculated coconut fiber and B. cereus stood out where nursery time was reduced by two months. Increments by 190% in IAA, 31% in GA3, and 17% in GA4 were found. This combination resulted in an increase by 98% in N, 42% in P, 82% in K, 103% in Ca, 68% in Mg, 84% in B, 41% in Fe, compared to control plants in coconut fiber+100% fertilization. Therefore, the use of B. cereus to obtain coconut seedlings is a technology that provides greater development in a shorter time in nursery and reduction in application of inputs.